Quantitative analysis of time-resolved microwave conductivity data. (10th November 2017) - Reid, Obadiah G; Moore, David T; Li, Zhen; Zhao, Dewei; Yan, Yanfa; Zhu, Kai; Rumbles, Garry
Abstract: Flash-photolysis time-resolved microwave conductivity (fp-TRMC) is a versatile, highly sensitive technique for studying the complex photoconductivity of solution, solid, and gas-phase samples. The purpose of this paper is to provide a standard reference work for experimentalists interested in using microwave conductivity methods to study functional electronic materials, describing how to conduct and calibrate these experiments in order to obtain quantitative results. The main focus of the paper is on calculating the calibration factor, K, which is used to connect the measured change in microwave power absorption to the conductance of the sample. We describe the standard analytical formulae that have been used in the past, and compare them to numerical simulations. This comparison shows that the most widely used analytical analysis of fp-TRMC data systematically under-estimates the transient conductivity by ~60%. We suggest a more accurate semi-empirical way of calibrating these experiments. However, we emphasize that the full numerical calculation is necessary to quantify both transient and steady-state conductance for arbitrary sample properties and geometry.